The relationship between quality of life in sarcopenia and skeletal muscle index in patients with advanced lung cancer - V. Kechedzhyiev (Kazimierz Wielki University, 2021)
Introduction. Today the relevance of sarcopenia is increasing in various types of malignant neoplasms.This syndrome is most common in patients with advanced forms of cancer and can adversely affect survival, treatment outcomes, and functional status. The prevalence of sarcopenia in patients with lung cancer is higher than in other types of malignant tumors. To understand the relationship between sarcopenia and quality of life is especially important for patients with advanced cancer. Aim. To assess the relationship between skeletal muscle index (SMI) and quality of life in sarcopenia in patients with advanced lung cancer. Materials and methods. A prospective analysis was carried out of 28 patients with advanced lung cancer who have applied to the "ONCOLIFE" Medical Center since the beginning of 2021. All patients had sarcopenia on CT scan. Skeletal muscle cross-sectional area analyzed using software ImageJ (National Institutes of Health, Bethesda, MD, USA). To determine the quality of life in sarcopenia a questionnaire SarQoL was used. Pearson's correlation analysis was used to assess the correlation between quality of life and SMI. Results. Pearson's correlation analysis showed a statistically significant positive correlation between quality of life and SMI (r = 0,451, р = 0,016, N=28). Body mass index (BMI) positively correlated with quality of life (r = 0,398, р = 0,036, N=28), and age negatively correlated with SMI (r = -0,391, р = 0,040, N=28). There was no statistically significant correlation between indicators such as BMI and SMI, as well as age and quality of life. Conclusions. Quality of life in sarcopenia statistically significantly correlates with SMI in patients with metastatic lung cancer. Early diagnosis of sarcopenia is essential for timely prescription of treatment aimed at maintaining and better muscle mass, which can improve cancer patients quality of life.